1974
DOI: 10.1172/jci107621
|View full text |Cite
|
Sign up to set email alerts
|

Hypophyso-Gonadal Function in Humans during the First Year of Life

Abstract: A B S T R A C T Total and unbound testosterone and A4-androstenedione have been determined in 104 cord blood samples. The same sexual steroids and pituitary gonadotropins have been measured in 46 normal male infants aged 27-348 days and 34 normal female infants aged 19-332 days.In cord blood of female neonates mean total and unbound testosterone was 29.6±7.5 and 0.89±0.4 ng/100 ml, respectively (mean±l SD); A4-androstenedione was 93±38 ng/100 ml. In male neonates mean plasma total and unbound testosterone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
173
1
7

Year Published

1975
1975
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 402 publications
(198 citation statements)
references
References 24 publications
17
173
1
7
Order By: Relevance
“…11,13,14 The sex difference seen in the present study might be caused by the different growth patterns of girls and boys, 25 which could reflect the anabolic effects of early infancy sex hormone production in males 26,27 or could be due to endocrinologic differences.…”
Section: Discussionmentioning
confidence: 69%
“…11,13,14 The sex difference seen in the present study might be caused by the different growth patterns of girls and boys, 25 which could reflect the anabolic effects of early infancy sex hormone production in males 26,27 or could be due to endocrinologic differences.…”
Section: Discussionmentioning
confidence: 69%
“…In this study only two patients; one of each group had their testis located in the abdomen, therefore the study is comparable also with regard to testicular position found at surgery. In male gonadotropin secretion which increases from 2 to 4 months after birth stimulating Leydig cells to secrete testosterone (12)(13)(14). Testosterone increase is blunted in cryptorchid boys (13,14).…”
Section: Commentsmentioning
confidence: 99%
“…By the end of the first trimester of fetal life, the gonadotrophin-releasing hormone (GnRH) pulse generator in the hypothalamus has developed and is functional [15][16][17][18][19]. Its activity will continue until about 6 months after birth in boys and 12-24 months in girls.…”
Section: Fetal and Early Neonatal Periodmentioning
confidence: 99%